Panic or peace - prioritising infant welfare when medicating feverish infants: a grounded theory study of adherence in a paediatric clinical trial - Eunicia Tan; Karen Hoare; Judith Riley; Kathryn Fernando; Libby Haskell; Christopher JD McKinlay; Stuart R Dalziel; Irene Braithwaite (BMC, 2022)
Abstract Background Literature on factors influencing medication adherence within paediatric clinical trials is sparse. The Paracetamol and Ibuprofen in the Primary Prevention of Asthma in Tamariki (PIPPA Tamariki) trial is an open-label, randomised controlled trial aiming to determine whether paracetamol treatment, compared with ibuprofen treatment, as required for fever and pain in the first year of life, increases the risk of asthma at age six years. To inform strategies for reducing trial medication crossovers, understanding factors influencing the observed ibuprofen-to-paracetamol crossovers (non-protocol adherence) is vital. The aim of this study was to investigate the factors influencing the decision-making process when administering or prescribing ibuprofen to infants that may contribute to the crossover events in the PIPPA Tamariki trial. Methods Constructivist grounded theory methods were employed. We conducted semi-structured interviews of caregivers of enrolled PIPPA Tamariki infants and healthcare professionals in various healthcare settings. Increasing theoretical sensitivity of the interviewers led to theoretical sampling of participants who could expand on the teams' early constructed codes. Transcribed interviews were coded and analysed using the constant comparative method of concurrent data collection and analysis. Results Between September and December 2020, 20 participants (12 caregivers; 8 healthcare professionals) were interviewed. We constructed a grounded theory of prioritising infant welfare that represents a basic social process when caregivers and healthcare professionals medicate feverish infants. This process comprises three categories: historical, trusting relationships and being discerning; and is modified by one condition: being conflicted. Participants bring with them historical ideas. Trusting relationships with researchers, treating clinicians and family play a central role in enabling participants to challenge historical ideas and be discerning. Trial medication crossovers occur when participants become conflicted, and they revert to historical practices that feel familiar and safer. Conclusions We identified factors and a basic social process influencing ibuprofen use in infants and trial medication crossover events, which can inform strategies for promoting adherence in the PIPPA Tamariki trial. Future studies should explore the role of trusting relationships between researchers and treating clinicians when conducting research.